PERANCANGAN BUKU FOTOGRAFI ESAI UPACARA ADAT KEBO-KEBOAN DESA ALASMALANG SEBAGAI UPAYA MENGENALKAN KEBUDAYAAN BANYUWANGI - Efendi, Wildan; Martono, Siswo; Yuan, Dhika (Jurnal Art Nouveau, 2017)
A Traditional Ceremony of Kebo-keboan is a ritual of bersih desa that was held in every Suro month in Java calendar which has a purpose to express thankfulness for God. Not only for expressing thankfulness but also most societies of Alasmalang Village have a role as a farmer, moreover, they have another purpose to refuse catastrophes or diseases that attacks their farmland and plantation. By doing the ceremony, the societies of Alasmalang Village believe that if the ceremony is done, they will avoid from the catastrophes which has attacked the village in the past. But the activities in this ceremony are just considered as an entertainment by visitors who come over without knowing the purposes in this Traditional Ceremony of Kebo-keboan.In this design of essay photography book of Traditional Ceremony of Kebo-keboan discusses the activities related to Traditional Ceremony in Alasmalang Village which is Kebo-keboan. By using essay photography technique and quotation in every photo of this book, it will make the readers easier to understand the activities of this ceremony.The existence of this traditional ceremony essay photography book of Kebo-keboan in Alasmalang Village, Banyuwangi, it also helps the readers to understand the activities of this ceremony, the readers are also respectively appreciate the culture which has derived by the ancestors in Indonesia.Keyword: Design of Essay Photography Book, Traditional Ceremony, Kebo-keboan, Alasmalang, Banyuwangi Culture.